Rare bird documentation form for Greater Scaup at DeSoto National Wildlife Refuge, 1983 - Bray, Tanyaet al (1983)
Rare bird documentation form for eleven Greater Scaups at DeSoto National Wildlife Refuge in Harrison County, IA on February 24, 1983. Epson - sheet feed